2008
DOI: 10.2214/ajr.07.2617
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Diffusion Tensor MRI in the Differential Diagnosis of Mild Cognitive Impairment and Alzheimer's Disease

Abstract: Diffusion tensor imaging is a promising technique for the evaluation of patients with probable mild cognitive impairment. Early detection of the disease expands the treatment options, increasing the likelihood of a good clinical response and enhancing the quality of life of patients and their relatives. Further studies with larger populations are needed to confirm the role of diffusion tensor imaging in the evaluation of memory impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
40
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 26 publications
9
40
0
3
Order By: Relevance
“…Furthermore, the findings of studies on more homogeneous patients, such as those with mild AD, are discrepant. For example, Xie et al [82] found a decrease of FA in the genu and left anterior body of the CC, whereas Ulkmar et al [83] found a decrease of FA in the genu and splenium of the CC; other studies [84][85][86][87] found no differences in the CC in patients with mild AD.…”
Section: Diffusion-weighted Imaging and Diffusion Tensor Imaging Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the findings of studies on more homogeneous patients, such as those with mild AD, are discrepant. For example, Xie et al [82] found a decrease of FA in the genu and left anterior body of the CC, whereas Ulkmar et al [83] found a decrease of FA in the genu and splenium of the CC; other studies [84][85][86][87] found no differences in the CC in patients with mild AD.…”
Section: Diffusion-weighted Imaging and Diffusion Tensor Imaging Studiesmentioning
confidence: 99%
“…At present, the DTI study results on MCI patients can be divided into two groups: 1) DTI studies on both amnesic and MCI "all subtypes" [23,40,41,84,85,88] that found no differences in MD and/or in FA in the CC compared with HC; and 2) the most recent studies [83,86,[89][90][91], which reported differences. One study on MCI "all subtypes" [89] found a significant change in MD and FA in the genu and the splenium of the CC in patients compared with HC.…”
Section: Diffusion-weighted Imaging and Diffusion Tensor Imaging Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The FA and MD values in patients with AD have been measured in several studies. While many studies have consistently demonstrated reduced FA and increased MD values in the hippocampus and temporal, frontal, and parietal lobes of patients with AD, [1][2][3][4][5] only a few studies have reported changes of the microstructural WM in patients with hydrocephalus by using DTI. 6,7 Moreover, it is not known whether the hippocampus is susceptible to iNPH.…”
mentioning
confidence: 99%
“…Similarly Wang et al (2009) and DiPaola et al (2010), using voxel based morphometry (VBM), identified a density reduction in the genu in aMCI patients compared with healthy controls. Other researchers like Ukmar et al (2008), Cho et al (2008) or Parente et al (2008) found an AF reduction in MCI patients in the CC splenium. The splenium of the corpus callosum, crux of the fornix (Zhuang et al, 2010) and the cingulum were sensitive discriminators to differentiante between aMCI and normal subjects (Chua et al, 2009).…”
Section: Diffusion Tensor Imaging (Dti)mentioning
confidence: 86%